The forgotten pillar: Strengthening the correctional subsystem in the integrated reform of the criminal justice system - Mulyadi Alrianto Tajuddin; Darmawati Darmawati; Rendie Meita Sarie Putri (Privietlab, 2025)
The Indonesian criminal justice system faces significant challenges related to the role and function of correctional institutions, which are still viewed as mere technical enforcers of punishment rather than integral parts of the rehabilitation and social reintegration process. This inequality results in high recidivism rates and failure to achieve true restorative justice, while also causing problems in enforcing prisoners human rights. This study aims to examine the structural disharmony between criminal justice subsystems and formulate an integrative model that positions correctional institutions as strategic actors in criminal policy and the implementation of restorative justice. The method used is normative legal research with a qualitative approach through an analysis of legislation, legal doctrine, and comparative studies of international correctional systems. Research findings show that marginalization in the criminal justice system exacerbates recidivism rates and weakens rehabilitative functions. The proposed integrative model places the correctional system as a partner from the early stages of the criminal process, including sentencing recommendations, risk assessments, and post-sentencing reintegration plans. This study reinforces the importance of functional equality between subsystems and the integration of restorative justice principles as the foundation for a more humane and effective criminal justice system reform in accordance with international human rights standards.